Hexyl alginate derivative, an amphiphilic innovative buccal film-forming material of promising mechanical and release characteristics for the improvement of repaglinide bioavailability - Khames A (Dove Medical Press, 2019)
Ahmed Khames1,2 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Beni-Suef University, Beni-Suef 62514, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, College of Pharmacy, Taif University, Taif 21974, Saudi Arabia Background: Association of long hydrocarbon chain with alginate molecule imparts surface active properties and increases chain flexibility. Purpose: This work studied the efficacy of synthesized hexyl alginate derivative as a film-forming material with unique amphiphilic and mechanical properties for the preparation of rapidly disintegrating repaglinide oral films with higher drug release rate and improved bioavailability. Methods: Alginate hexyl amide derivative was prepared and used in the formulation of oral films by solvent casting technique. Using Box–Behnken experimental design, formulations were optimized at different polymer, plasticizer, and disintegrant levels as independent variables for maximum drug release rate, higher tensile strength, and shortest disintegration time as responses. Optimized film formulae were fully evaluated and subjected to further in vivo bioavailability studies in rabbits. Results: Higher dependency of response results on the selected variables was observed. Optimized formula showed satisfactory tensile strength (145.862 g/cm2), rapid disintegration (22.2 seconds), and higher drug release rate (97.799% within 30 minutes). The drug bioavailability was significantly improved in comparison with plain drug and conventional alginate oral films, where the AUC and Cmax values reached 296.072 µg.h/mL and 116.932 µg/mL in comparison with 164.917 µg.h/mL and 56.568 µg/mL for alginate film and 95.368 µg.h/mL and 31.925 µg/mL for plain drug, respectively. Tmax also showed significant reduction to be only 30 minutes in comparison with 60 minutes for other forms. Conclusion: This led to the final conclusion that the synthesized alginate derivative is an innovative promising film-forming material with unique mechanical and drug release properties for application in buccal drug delivery especially of Biopharmaceutics Classification System (BCS) class II drugs to increase solubility and improve bioavailability. Keywords: amphiphilic derivatives of alginate, Box–Behnken, BCS class II drugs, oral films, repaglinide